PENGARUH AUDIT TENURE, REPUTASI KAP DAN AUDIT FEE TERHADAP AUDIT DELAY (STUDI EMPIRIS PADA PERUSAHAAN CONSUMER GOODS YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2020) - Tushafa, Muhammad Giri Fadhila; Widiyati, Dian (Publika Citra Media, 2025)
The purpose of this study is to determine whether the variable of audit tenure, KAP reputation, and audit fees have an effect on audit delay through empirical studies on consumer goods companies on the Indonesia Stock Exchange in 2018-2020. This type of research is descriptive quantitative research with data collection method using purposive sampling and using pool data analysis with E-Views ver. 10 as the analysis tool. The research population is consumer goods companies with a total of 75 companies on the Indonesia Stock Exchange and 35 samples of companies are obtained with an observation period of 3 years, 2018-2020. The results show that the audit tenure variable partially had effect on audit delay, while the KAP reputation variable and audit fee variable partially had no effect on audit delay, and the audit tenure, KAP reputation, and audit fee simultaneously effect on audit delay.